CODE SWITCHING AS POLITENESS STRATEGIES IN EFL CLASSROOM INTERACTION - Darwis, Nirwana (English Review: Journal of English Education, 2024)
Code switching and Politeness strategy are elements of communication that significantly influence classroom interaction. This paper was to reveal code switching including the reason of code switching as well as how it functions as politeness strategy in EFL classroom interaction. This study adopted a qualitative descriptive method. This research was based on the observation conducted in Universitas Negeri Makassar, in 2022. The research subject was 2 English Education classes that employed group presentation as the learning strategy. It consisted of 31 students for each class. To collect the data, the researcher recorded the classroom presentation. The recordings were then transcribed and analyzed by using discourse analysis approach. The reason of code switching was analyzed based on the theory by Hoffman (1991), and the politeness strategy was based on the rule of Politeness strategy by Brown and Levinson (1987). The result showed that code switching was used by students as politeness strategy during group presentation, and it was reflected in some maxims that were maxim of manner, maxim of relation, quality maxim, and quantity maxim. Finding of this research was significant in expanding ideas and insight about code switching that is actually can be used as politeness strategy in classroom interaction, particularly in group presentation.